2009
DOI: 10.1179/102453309x12473408860226
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of V617F mutation of the JAK2 gene in patients with chronic myeloproliferative disorders

Abstract: We found an association between JAK2 V617F and thrombotic events in patients with PV and ET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
4
17
0
2
Order By: Relevance
“…Campbell et al [13] [15]. Several studies have shown that the prevalence of the JAK2 V617F mutation in ET is ranging approximately from 23 to 69 % [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In the present study, the frequency of JAK2 V617F mutation positive was 46 % in ET, which is consistent with the studies in the literatures.…”
Section: Discussionsupporting
confidence: 95%
“…Campbell et al [13] [15]. Several studies have shown that the prevalence of the JAK2 V617F mutation in ET is ranging approximately from 23 to 69 % [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In the present study, the frequency of JAK2 V617F mutation positive was 46 % in ET, which is consistent with the studies in the literatures.…”
Section: Discussionsupporting
confidence: 95%
“…From previous reports, megakaryopoiesis was enhanced when the progenitors are heterozygous for JAK2 V617F, whereas erythropoiesis is strongly stimulated when the progenitors are homozygous for the JAK2 V617F mutation [19]. In this study, patients with the JAK2 V617F mutation had an increased platelet count compared to those with wild-type JAK2, which was consistent with the results of a previous study [20]. These data suggest that the pathogenesis of thrombocytosis in patients with these 4 diseases might be similar to that in the case of essential thrombocytosis.…”
Section: Discussionsupporting
confidence: 92%
“…In another study for ET patients [21], no significant difference was found for WBC counts in the mutated and wild-type groups. However, Ana L. Basquiera et al [22] reported that WBC counts and Hb were significantly higher in JAK2 V617F mutated group than that in wild-type group in ET and PV patients, but platelet counts showed no significant difference. Therefore, the relationship between JAK2 V617F and hemogram variation was controversial, and no investigation has been performed to determine the JAK2 V617F mutation rate in patients groups classified by RBC counts, WBC counts, platelet counts and lineage hyperplasia state.…”
Section: Introductionmentioning
confidence: 94%